Effects of Tao‐Hong‐Si‐Wu decoction on acute blood stasis in rats based on a LC‐Q/TOF‐MS metabolomics and network approach - Ma, Qi; Li, Peng‐Ling; Hua, Yong‐Li; Ji, Peng; Yao, Wan‐Ling; Zhang, Xiao‐Song; Zhong, Li‐Jia; Wei, Yan‐Ming (Biomedical chromatography, 2018)
A novel approach using metabolomics coupled with a metabolic network was used to investigate the effects of Tao‐Hong‐Si‐Wu decoction (THSWD) on the rat model of acute blood stasis syndrome. Acute blood stasis syndrome was induced by placing the rats in ice‐cold water following two injections with epinephrine. The hemorheological indicators [whole blood viscosity (WBV) and plasma viscosity (PV)] and the blood coagulation indicators [thrombin time (TT), prothrombin time (PT), activated partial thromboplastin time (APTT) and fibrinogen (FIB)] were detected. The nonparametric univariate method and multivariate statistical analysis were performed for determining the potential biomarkers. A correlation map was structured between biochemical indicators and hub metabolites to explain the effects mechanism of THSWD. After the administration of THSWD, the levels of WBV, PV, TT, APTT and FIB returned to levels observed in the control group. According to metabolomics coupled with metabolic network analysis, the intervention of THSWD in rats with acute blood stasis syndrome induced substantial and characteristic changes in their metabolic profiles. Fifteen metabolites were screened, which mainly involved 10 pathways and five hub metabolites, namely, l‐glutamate, l‐phenylalanine, N‐acylsphingosine, arachidonic acid and phosphatidate. The biochemical indicators and hub metabolites could be adjusted to close to normal levels by THSWD. Therefore, combining metabolomics and metabolic network helped to evaluate the effects of THSWD on acute blood stasis.